Penerapan Algoritma Liniear Congruential Generator Pada Aplikasi Susun kata Pengenalan Budaya Di Indonesia - S, Alyuda Saputra; Sauda, Siti (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Indonesia, namely, an archipelagic country that has a variety of cultures and so many tribes. But most of us don't realize that. For this reason, we need to cultivate a sense of nationalism and love for the homeland from an early age, especially young people in Indonesia. Most people in the school environment only use books to study it and only make students bored quickly. There are many ways that teachers or parents must do by using a mobile phone. The development of the mobile phone, media, which is one part of a medium for delivering information, which is currently an alternative new method that can be used as a means of delivering information in an attractive, easily accessible, and clear form. It can also help all people to know the various cultures in Indonesia. Therefore, an android-based application was made, namely the Application of the Linear Congruential Generator Algorithm in the Introduction to Culture in Indonesia, in order to help and make it easier to find out about culture in Indonesia. The Linear Congruential Generator (LCG) method is a randomization algorithm used to generate a random number (Random Number). From the results of the research that has been carried out, it shows that the Linear Congruential Generator (LCG) method is very effectively applied in randomizing letters and questions.